TIME DEPENDENT DEFLECTION OF A FLOATING ICE SHEET. - Nevel,Donald E. (1966)
A solution for a viscoelastic plate on an elastic foundation is presented for an infinite bulk modulus and a shear modulus which obeys Maxwell's model. Observed deflections of a floating ice sheet agree with this solution. A solution for a viscous shear modulus is also presented. (Author)